The Failure of a Success Story: Reforming Georgia’s Public Service Broadcaster - Bekerman, Marek (Global Media Journal - German Edition, 2015)
Georgia’s “Law on Broadcasting” was passed in 2004 to provide, among other things, a legal framework for the transformation of the country’s state broadcaster into the public service media provider. The law itself has been praised internationally for its progressive nature and presented as an example for other post-Soviet countries to follow. A decade later, and after a number of amendments, it is no longer seen as effective in ensuring that public service broadcasting in Georgia provides the expected quality and range of services, or can be immune to political interference. Since its birth, GPB has suffered from continuous crises and scandals, and has never been a major player in the Georgian media. There have been several attempts involving international organisations and institutions to reform and improve GPB, to elevate its status and increase its market share, but none of them have succeeded. Most of those efforts have been supported by the European Commission and the OSCE, with participation from such media organisations as the BBC, which had run a series of training and monitoring programmes until 2011. A comprehensive programme of editorial, managerial and structural reform at the Georgian broadcaster developed in 2011-12 was shelved ahead of parliamentary and presidential elections, and GPB has been in a state of semi-paralysis ever since. The article examines the state of public service broadcasting in Georgia and what could be done to improve it.